To Save from Oblivion. They Lived for the Church and the World - Rozen, Barbara (Studia Warmińskie, 2012)
To save from oblivion. They lived for Church and the world is the article commemorating the activity of Józef Wojtukiewicz Rev. and Adela Stefanowicz, who after World War II struggling against many financial, social and political difficulties, in hard and even dramatic conditions laid the foundation of developing catechetic theory and practice. Meeting those both great personalities was inspiring. Their cooperation bore fruits in numerous research concerning integral upbringing and methodology of educational work, especially catechetic one. They founded Catholic Institute in Czestochowa in 1945 just after World War II – the first high theological school for laymen. In after war Poland communist authorities hindered religious activity and therefore the Institute had to change its location very often. The work of the Institute developed in two directions: theoretic – scientific and training and practical. The Institute delivered for Polish Church well prepared and spiritually formed catechists and equipped them with practical aids for teaching religion at different levels. Spiritual ideals of both of them, their devotion for God and caring about a human being connected with common activity brought about measurable effects. Together with the Institute the community of secular institute of consecrated life was founded and developed.